2018
DOI: 10.1093/pcp/pcx211
|View full text |Cite
|
Sign up to set email alerts
|

Three Fatty Acyl-Coenzyme A Reductases, BdFAR1, BdFAR2 and BdFAR3, are Involved in Cuticular Wax Primary Alcohol Biosynthesis in Brachypodium distachyon

Abstract: Plant cuticular wax is a heterogeneous mixture of very long chain fatty acids (VLCFAs) and their derivatives. Primary alcohols are the dominant wax components throughout leaf development of Brachypodium distachyon (Brachypodium). However, the genes involved in primary alcohol biosynthesis have not been investigated and their exact biological function remains unclear in Brachypodium to date. Here, we monitored the leaf wax profile and crystal morphology during Brachypodium leaf morphogenesis, and isolated three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…In our study, to assess the influence of drought stress on leaf cuticular wax accumulation in B. distachyon , both water deficit and PEG treatments were performed. Results showed that the cuticular wax of control plants mainly contained primary alcohols, alkanes, aldehydes, and fatty acids, in which primary alcohols were dominant components with few contents of other compounds ( Figure 1 ), which is consistent with the results of a recent study that the leaf cuticular wax of B. distachyon mainly consists of primary alcohols with less contents of aldehydes, alkanes, and fatty acids throughout leaf development (Wang et al, 2018). All treatments resulted in significant increases of total wax load and individual compound without changing wax composition ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, to assess the influence of drought stress on leaf cuticular wax accumulation in B. distachyon , both water deficit and PEG treatments were performed. Results showed that the cuticular wax of control plants mainly contained primary alcohols, alkanes, aldehydes, and fatty acids, in which primary alcohols were dominant components with few contents of other compounds ( Figure 1 ), which is consistent with the results of a recent study that the leaf cuticular wax of B. distachyon mainly consists of primary alcohols with less contents of aldehydes, alkanes, and fatty acids throughout leaf development (Wang et al, 2018). All treatments resulted in significant increases of total wax load and individual compound without changing wax composition ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, three BdFAR genes ( BdFAR1 , BdFAR2 , and BdFAR3 ) have been demonstrated to be involved in the alcohol-forming pathway and they respond to abiotic stresses in B. distachyon (Wang et al, 2018). These results together suggest that the cuticular wax biosynthetic pathways in B. distachyon are similar to those in Arabidopsis, containing both the alcohol-forming and the alkane-forming pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also shown that the number of FAR genes and their functions may vary, according to species-specific genetics. In other crops, it is evident that FAR2 and FAR3 are responsible for the biosynthesis of C 26 and C 28 primary alcohols [41]. Another report has claimed that at least five FARs are responsible for primary alcohol (C 16 to C 28 ) biosynthesis in Aegilops tauschii [42].…”
Section: Discussionmentioning
confidence: 99%